Relationship Between Social Capital and Depressive Symptoms Among Type 2 Diabetes Mellitus Patients in Northwest China: A Mediating Role of Sleep Quality - Wang, Liqun; Li, Jiangping; Dang, Yuqi; Ma, Haiyu; Niu, Yang (Frontiers in Psychiatry, 2021)
Objective There are few studies about the relationship between social capital (SC) and depression among type 2 diabetes mellitus (T2DM) patients and the mechanism explaining how SC leads to decreased depression is unclear. The current study aims to explore the relationship between social capital and depressive symptoms among the T2DM patients in northwest China, with a particular focus on the mediating role of sleep quality. Methods A cross-sectional study of 1761 T2DM patients from Ningxia province was conducted. The Center for Epidemiological Survey Depression Scale (CES-D), self-report sleep quality questionnaire coupled with the social capital scales administered during the face-to-face survey. The Bootstrap methods PROCESS program is employed to test the mediation model. Results The prevalence of depressive symptoms among T2DM patients was 24.8%. After controlling for covariates, the SC (r=-0.23, P<0.001) was negatively correlated with CES-D score; the sleep quality was also negatively correlated with CES-D score (r=-0.31, P<0.001); and the SC was positively correlated with sleep quality (r=0.10, P<0.001). Logistic regression analysis showed SC was inversely related to the risk of depressive symptoms. Meanwhile, sleep quality was negatively associated with depressive symptoms. Sleep quality has mediated the relationship between SC and depressive symptoms among T2DM patients (explaining 12.6% of the total variance). Conclusions We elucidated how SC interacted with depressive symptoms through the mediation pathway of sleep quality using a representative sample of the Chinese diabetes patients. The findings indicate the improvement of SC and sleep quality may help in maintaining mental health among T2DM patients. Hence, clinicians can suggest patients communicate more with others to improve the social capital, and in turn maintain their health.